New biochips for a three-dimensional study of transendothelial leukocyte migration - Toetsch, Stéphanie (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2011)
An important step in the inflammatory response is the recruitment of leukocytes into tissues through the endothelial cells which line blood vessels. Transendothelial migration (TEM) is the result of a multistep cascade in which chemoattractant gradients mediate the migration of leukocytes through the endothelial wall and into the underlying tissue. The leukocyte transendothelial migration is a small part of the processes that comprises the immune system. However cell migration through the endothelium plays a role in the progression of diverse diseases, such as cancer metastasis and atherosclerosis, or physiological processes, such as embryonic morphogenesis and wound healing. It is necessary to understand the mechanisms of this migration in order to establish, through research, how to support, supplement and improve its fiinction.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin